A classroom based intervention in conflict affected Poso, Indonesia: synthesising lessons learned from research and practice. Issue 1 (March 2016) - Susanty, Dessy; Jordans, Mark J. D.; Irmayani, Rima; Tol, Wietse A.
Abstract : This paper describes lessons learned from a classroom based intervention, which was implemented in the post conflict area of Poso, Indonesia. These lessons are drawn from qualitative research and a randomised controlled trial in the area, as well as data from our own programme monitoring and evaluation. We describe these lessons learned from a socio-ecological perspective, making recommendations to strengthen the classroom based intervention's connection with critical mental health and psychosocial issues relevant at individual, family and wider community levels. Lessons learned include: the need for further adaptations to address local somatic expressions of psychological distress; consideration of changes at the cognitive level; a need for gender specific activities; engaging families in school based interventions; and addressing the damage to the wider social fabric, including at peer level. The engagement of trained paraprofessional health care is also discussed as an essential consideration.